Correlation between C-Reactive Protein Level and Blood Urea Nitrogen-Creatinine Ratio in COVID-19 Patients - Meta Safitri; Lisyani Budipradigda Suromo (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
Coronavirus Disease 2019 (COVID-19) is caused by Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-CoV-2).C-Reactive Protein (CRP) is an inflammation marker that increases significantly in COVID-19 patients. SARS-CoV-2 can affectkidney function and increase the Blood Urea Nitrogen (BUN)-creatinine ratio. The previous study showed that CRP andBUN-creatinine ratios could be used as predictors of the severity and survival of COVID-19 patients. This study aimed todetermine the correlation between CRP levels and the BUN-creatinine ratio in COVID-19 patients. A retrospectivecross-sectional study was conducted on 34 COVID-19 patients who were diagnosed by PCR test at Dr. Kariadi Hospital,Semarang from March to September 2020. The Spearman correlation test was used for statistical analysis. The median CRPvalue was 4.59 (0.36-27.48) mg/L and BUN-creatinine ratio was 15.06 (5.79-37.04), while the correlation between CRP andBUN-creatinine ratio showed p=0.003 and r=0.502. There was a moderate positive correlation between CRP level andBUN-creatinine ratio. C-reactive protein plays a role in the infiltration process of inflammatory cells and increases adhesionmolecules, which can directly or indirectly damage kidney function. SARS-CoV-2 can enter the kidney directly through theACE-2 receptor and activate the renin-angiotensin-aldosterone system, which will increase water and sodium absorption inthe renal tubules, passive reabsorption of BUN, and creatinine filtration in the glomerulus resulting in increasedBUN-creatinine ratio.